Supernova lightCURVE POPulation Synthesis I: Including interacting binaries is key to understanding the diversity of type II supernova lightcurves. (31st December 2018) - Eldridge, J. J.; Xiao, L.; Stanway, E. R.; Rodrigues, N.; Guo, N.-Y.
Abstract: We present results of a supernova lightcurve population synthesis, predicting the range of possible supernova lightcurves arising from a population of progenitor stars that include interacting binary systems. We show that the known diversity of supernova lightcurves can be interpreted as arising from binary interactions. Given detailed models of the progenitor stars, we are able to the determine what parameters within these stars determine the shape of their supernova lightcurve. The primary factors are the mass of supernova ejecta and the mass of hydrogen in the final progenitor. We find that there is a continuum of lightcurve behaviour from type IIP, IIL, to IIb supernovae related to the range of hydrogen and ejecta masses. Most type IIb supernovae arise from a relatively narrow range of initial masses from 10 to 15 M⊙ . We also find a few distinct lightcurves that are the result of stellar mergers.